PENINGKATAN KESADARAN LINGKUNGAN ANGGOTA IKATAN MAHASISWA MUHAMMADIYAH MELALUI PENGOLAHAN SAMPAH ORGANIK DENGAN TEKNOLOGI TAKAKURA - Priantari, Ika; Setyowati, Trias (Universitas Mataram, 2024)
This endeavor regarding environmental sustainability is consistently produced by IMM Jember Regency. Including organic waste management can be done with simple, cheap, effective and efficient technology by IMM. It's just that IMM environmental activists still do not have the standard ability to educate the public to apply this Takakura technology. The identification results show that there are two problems faced by members of the Muhammadiyah Student Association of Jember Regency, namely first, IMM activists do not understand how Takakura technology works, secondly IMM activists still do not have the skills to apply this Takakura technology. The purpose of this activity is first, to improve the understanding of IMM activists about takukura technology. The second objective is to improve the skills of IMM activists to apply Takakura technology. Methods of Implementation Activities are carried out by preparing tools and materials, providing guidance and counseling, providing and simulating the making of Takakura technology. At the end of the activity, an evaluation of the success of the community service program was carried out. The process and stages of applying Takakura technology given to the Environmental activists of the Muhammadiyah Student Association have been able to improve the ability of participants very significantly. Therefore, this activity is considered to have succeeded in empowering environmental activists of the Muhammadiyah Student Association of Jember Regency.